Kenakalan Remaja, Perkembangan dan Upaya Penanggulangannya - Hairus Sodik; Fathor Arifin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2022)
AbstractJuvenile delinquency has now almost occurred in every corner of the country, from light acquaintances such as disobedience to parents and teachers, often skipping school, and severe juvenile delinquency such as behavior that deviates from criminal law that disturbs others such as stealing, pointing, speeding. speeding, drinking alcohol, to the abuse of narcotics, and having free sex. The causes of juvenile delinquency include internal and external factors. Other influences are also due to family, school and community factors. So to overcome this, it is necessary to guide parents, schools, and a good environment to help adolescents experience good development.Key words: Juvenile delinquency, morals, Countermeasures